Mapeamento Ambiental Como Proposta Para a Construção dos Conceitos de Biodiversidade e Cerrado no Ensino Ensino de Biologia - CASTRO, Shaleny Costa Pereira (2009)
This study aimed to investigate the effectiveness of environmental mapping tool for building biological concepts Biodiversity and Cerrado students in the 2nd year of high school, in the discipline of Biology. The methodology used in this study was the participant research, where he sought to break with the dyad between subject and object and theory and practice, common features in traditional searches, so there was the construction of a more solid knowledge from a more fruitful relationship between subject-subject. Thus, it was possible to promote the critical linking between scientific knowledge and the understanding of common sense by bringing the reality of daily life of the participants themselves. Three questionnaires were applied, being the first to evaluate the proficiency level of students on the Biodiversity and Cerrado concepts and the other two questionnaires were after discussion on those concepts. The questionnaire II was applied to half of the students who participated in the research after the theoretical class, in order to verify students learning after this exposition, without completing the environmental mapping. The third questionnaire was applied to the other half of the class after the completion of the environmental mapping, with the objective of verifying the effectiveness of this activity to learn the concepts proposed. The three questionnaires were compared so that we could assess the learning concepts of Biodiversity and Cerrado. To supplement the data acquired with the questionnaires, we conducted a technique that consists of a group interview, called the focus group in order to capture immediate and consistently the information desired by intensifying the points raised by the questionnaires. The comparing the questionnaires II and III to questionnaire I, we could prove the effectiveness of the environmental mapping concepts for the construction Biodiversity and Cerrado. Most of the students had some increase in their knowledge about these concepts, especially after the mapping. Analyzing and comparing the questionnaires, it is remarkable the conceptual change in relation to the previous knowledge that students had on biodiversity and Cerrado presented in the questionnaire I. In the questionnaire II and III students had more answers close to those considered scientifically accurate, showing that there was a reorganization or rejection of the previously existing concepts. The focal group interview also confirmed the effectiveness of environmental mapping tool for acquiring this concepts, as identified in the analysis of questionnaires. This tool enabled the approach of students to the environment around the school, making the lessons more contextualized and interdisciplinary, seeking overcome challenges and contradictions raised for the Teaching of Biology. The environmental mapping, inserted in the school practice, made possible the understanding of the scientific knowledge, allowing its relationship with the everyday life of students giving then a chance of using it in different situations of life, and allow students to guide and have a position before issues that can interface with their living conditions and in their daily actions.